Flint vs. Limestone – A comparative analysis on the development of macro-wear traces: Implications for the analysis of ancient lithic toolkits - Viallet, Cyril (Journal of Lithic Studies, 2021)
Especially for the Lower Palaeolithic, traceological analysis is very difficult to carry out due to bad preservation and the diversity of raw materials used for tool production. Due to the problem of preservation, focuses the functional analysis on the observation of macro-wear appears to be a good solution to the challenge of obtaining functional data. We propose thus to present the results of a large experiment (up to 300 experimental tools), conducted with limestone and flint flakes. Controlled parameters were disposed to provide replicative criteria for comparison. Three movements were performed systematically (longitudinal action, and transversal action both unidirectional and bidirectional), across two durations. In the first stage, actions were realised on the same worked material: dry wood calibrated. Each raw material for each action was represented by 48 experimental tools. In the second stage (63 experimental tools), the same actions were realised on different worked materials such as fresh wood, skin, bone, meat, and others. The macro-wear traces produced (mainly micro-flakes) were described relative to their position on the edge and their morphology. The comparison between the two raw materials was made using a statistical approach. The results were discussed under the influence of different parameters: morphology of the cutting edge, duration of use and edge angle of the active part. These results confirm firstly that macro-wear is reliable in determining the tool movement. Moreover, as assessed by the chosen criteria, only a few differences exist in the macro-wear development between flint and limestone. Finally, we conclude that the micro-flakes provide relevant information and should be used more frequently for functional analysis of ancient and badly preserved material.